2020
DOI: 10.1515/tnsci-2020-0111
|View full text |Cite
|
Sign up to set email alerts
|

Deviant cortical sulcation related to schizophrenia and cognitive deficits in the second trimester

Abstract: ObjectivesAberrant cortical development, inferred from cortical folding, is linked to the risk of schizophrenia. Cortical folds develop in a time-locked fashion during fetal growth. We leveraged this temporal specificity of sulcation to investigate the timing of the prenatal insult linked to schizophrenia and the cognitive impairment seen in this illness.MethodsAnatomical MRI scans from 68 patients with schizophrenia and 72 controls were used to evaluate the sulcal depth of five major invariable primary sulci … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These studies may not be comprehensive enough to study the neurodevelopmental mechanism of schizophrenia owing to the limitation of the studied brain regions and the sample inconsistency. A study indicated that the gestational disruption underlying schizophrenia is likely to predate, and the burden of cognitive damages may be associated specifically with the aberrant superior frontal development, which is apparent in late second trimester [40], suggesting that brain sulcus depth changes in the olfactory and superior frontal may be involved in the development of schizophrenia. Additionally, the frontal lobe plays a critical role in the integration and regulation of higher neural activities in humans [41].…”
Section: Discussionmentioning
confidence: 99%
“…These studies may not be comprehensive enough to study the neurodevelopmental mechanism of schizophrenia owing to the limitation of the studied brain regions and the sample inconsistency. A study indicated that the gestational disruption underlying schizophrenia is likely to predate, and the burden of cognitive damages may be associated specifically with the aberrant superior frontal development, which is apparent in late second trimester [40], suggesting that brain sulcus depth changes in the olfactory and superior frontal may be involved in the development of schizophrenia. Additionally, the frontal lobe plays a critical role in the integration and regulation of higher neural activities in humans [41].…”
Section: Discussionmentioning
confidence: 99%
“…Gyrification patterns are established predominantly in the late second to third trimesters of pregnancy and remain relatively stable after postnatal week; 6 , 10 , 11 aberrant gyrification in adults with schizophrenia is often interpreted as a sign of an in utero pathology 12 . This interpretation is supported by studying obstetric complications; preterm-born adults show widespread reductions in gyrification similar to the pattern seen in patients with established schizophrenia 13 .…”
Section: Introductionmentioning
confidence: 99%